THE EFFECT OF QUIZIZZ APPLICATION LEARNING MEDIA ON MOTIVATION AND LEARNING OUTCOMES OF CLASS X HISTORY OF SMK 2 PANCASILA: PENGARUH MEDIA PEMBELAJARAN APLIKASI QUIZIZZ TERHADAP MOTIVASI DAN HASIL BELAJAR SEJARAH KELAS X SMK 2 PANCASILA - Ervin Dwiastuti; M. Iqbal Ibrahim Hamdani; Agi Ma’ruf Wijaya (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This study aims to analyze the effect of the quizizz application learning media on the motivation and learning outcomes of class X history of SMK 2 Pancasila. The focus of the study was to see the extent to which the quizizz learning media influenced the motivation and learning outcomes of students. The research method used a Pre-Experimental Design type two group posttest-only design with a quantitative approach. There were control and experimental classes to prove the action hypothesis that there was a significant effect of the use of quizizz media between the two groups. Data collection techniques were in the form of learning motivation questionnaires and test questions to determine learning outcomes. Data analysis used a scoring technique with a Likert scale, normality test, homogeneity test, and hypothesis test, all of which were processed using the SPSS version 25 application. The results of the study were that in the control class the highest score was 70 and after being given treatment in the experimental class the score became 100, then the average obtained from the control class was 60.2 and in the experimental class it became 89.0. The value of the motivation questionnaire r count is 0.0713 and the value of r table = 44, and the Posttest r count is 0.0601 and the value of r table = 44, and the significance value is 0.05 so that H0 is accepted. And the value of the motivation questionnaire is 0.0713 then H0 is accepted because >0.05, and the posttest value is 0.0601 then H0 is accepted because >0.05. So it can be concluded that with the treatment of learning media using quizizz in History subjects, it has an impact on increasing values ​​significantly, students are more motivated in learning History by completing History assignments and questions well, so it can be concluded that the quizizz learning media provides high interest and motivation in learning History.